Putusan Perkara Nusyūż Akibat Kekerasan Dalam Rumah Tangga (KDRT): Kajian Sosiologi Hukum - Fitriyani Fitriyani (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2022)
This study aims to determine how the judge’s sociological perspective affected his ruling in the nusyūż case due to the occurrence of domestic violence (KDRT). The study's research topics are: (1) how are the arguments of the judges of the Religious High Court (PTA) in deciding cases of nusyūż due to domestic violence; and (2) How do judges’ sociological perspectives argue when making decisions in cases of domestic violence in the PTA. The data is derived from the Palembang Religious High Court decision No.21/Pdt.G/2018/PTA.Plg and the Banjarmasin Religious High Court decision No.44/Pdt.G/2019/PTA.Bjm, both of which were obtained from the Supreme Court of Indonesia’s website. Data were analyzed utilizing juridical and sociological approach through content analysis. The study’s findings revealed that the understanding of the husband’s superiority over his wife was a factor in the occurrence of Domestic Violence, as seen in PTA Palembang and Banjarmasin decisions, which was caused by frequent quarrels/bickering between husband and wife, which led to violence against the wife both physically and verbally. The passage of the Qur’an surah an-Nisa/4:34 discussing the completion of a wife’s nusyūż by hitting has influenced public perception, granting validity to a husband’s beating of his wife.